Single dose of inducible nitric oxide synthase inhibitor induces prolonged inflammatory cell accumulation and fibrosis around injured tendon and synovium. Issue 3 (2004) - Darmani, Homa; Crossan, James C.; Curtis, Adam
Abstract : THE aim of the current study was to investigate the effect of inhibition of nitric oxide (NO) production after injury on inflammatory cell accumulation and fibrosis around digital flexor tendon and synovium. A standard crush injury was applied to the flexor tendons of the middle digit of the hindpaw and the overlying muscle and synovium of female Wistar rats. Thirty animals received an intraperitoneal injection of either isotonic saline or N (G)-nitro-l-arginine methyl ester (L-NAME; 5 mg/kg) immediately following the crush injury, and five animals were then sacrificed at various intervals and the paws processed for histology. Another group of five animals was sacrificed after 3 days for nitrite determinations. The results showed that nitrite production and hence NO synthase activity is doubled at the acute phase of tendon wound healing, and we can prevent this by administering a single dose of L-NAME immediately after injury. The incidence and severity of fibrocellular adhesions between tendon and synovium was much more marked in animals treated with L-NAME. Treatment with L-NAME elicited a chronic inflammatory response characterised by a persistent and extraordinarily severe accumulation of large numbers of inflammatory cells in the subcutaneous tissues, in muscle and in tendon. These findings indicate that in the case of injured tendon and synovium, NO could act to protect the healing tissue from an uncontrolled inflammatory response.